2008
DOI: 10.1163/156853708x358173
|View full text |Cite
|
Sign up to set email alerts
|

Human Spatial Behaviour: The Spacing of People, Objects and Animals in Six Cross-Cultural Samples

Abstract: Th is study examines the principles we apply, when people, objects and animals are to be organized in relation to other representatives of their kind. Most cross-cultural studies on personal space focus on cultural diff erences, but here we look for proxetics (universals) as well as proxemics (cultural diff erences). 793 subjects from six countries (Greenland, Finland, Denmark, Italy, India and Cameroon) situated in four diff erent climate zones are tested with a projective simulation measure (the 'IPROX'). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Interactions occurring within the space near the body have been studied in a range of disciplines, including ethology, neurophysiology, social science, architecture, and philosophy 1 , 2 , 3 , 4 , 5 . Such studies have shown that many behavioural responses are increased when stimuli occur near the body.…”
Section: What Is Peripersonal Space?mentioning
confidence: 99%
“…Interactions occurring within the space near the body have been studied in a range of disciplines, including ethology, neurophysiology, social science, architecture, and philosophy 1 , 2 , 3 , 4 , 5 . Such studies have shown that many behavioural responses are increased when stimuli occur near the body.…”
Section: What Is Peripersonal Space?mentioning
confidence: 99%
“…Also, individuals from contact cultures would be more tolerant to crowded situation than individuals from non-contact cultures. This distinction is supported by findings of, amongst others, Aiello (1987), Remland, Jones and Brinkman (1995) and Høgh-Olesen (2008). For instance, Høgh-Olesen examined personal space preferences in several countries and found that participants from Greenland, Finland and Denmark systematically maintained a larger interpersonal distance than participants from Italy, India and Cameroon.…”
Section: Cultural Influences On Spaciousness Needssupporting
confidence: 55%
“…Besides evolution, another important determinant of spaciousness preferences is one's cultural background. Although little to no research can be found that examines cultural differences in spaciousness perceptions, research focusing on personal space provides evidence for a cultural influence on experienced spaciousness (Aiello, 1987;Altman, 1975;Hall, 1965;Hall 1966;Høgh-Olesen, 2008;Remland, Jones & Brinkman, 1995). For instance, Hall (1966) distinguishes non-contact (e.g., Northern European, Northern American) and contact (e.g., Mediterranean, Arabic, Hispanic) cultures.…”
Section: Cultural Influences On Spaciousness Needsmentioning
confidence: 99%
“…An indication of whether participants were members of a highcontact or low-contact culture was assessed by measuring closeness as people from a high-contact culture have been found to sit significantly closer to each other compared with members from a low-contact culture [19]. Five items from the IPROX (iconic proximity) questionnaire were used [7]. Participants' general attitude towards robots was measured by the Negative Attitude Towards Robots scale, a 14-item 7-point Likert scale.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…When this buffer zone is invaded, people compensate for this intimate contact, by non-verbal or verbal compensation behaviors such as stepping away, or limiting eye contact [14]. While every human adheres to others' personal space, what individuals regard as appropriate distances in certain social situations depends on culture [e.g., [19], [7], [17]). …”
Section: Introductionmentioning
confidence: 99%